Long-term river invertebrate community responses to groundwater and surface water management operations. (1st February 2021) - White, J.C.; Fornaroli, R.; Hill, M.J.; Hannah, D.M.; House, A.; Colley, I.; Perkins, M.; Wood, P.J.
Highlights: Long-term biomonitoring data was combined with regional groundwater model outputs Anthropogenic flow alterations yielded non-significant ecological effects in most instances Some ecological metrics peaked when discharges were reduced by c. 0-15% Invertebrate communities sampled in spring were most responsive to flow variability Water management operations largely supported key riverine ecological assets Abstract: River flow regimes have been transformed by groundwater and surface water management operations globally, prompting widespread ecological responses. Yet, empirical evidence quantifying the simultaneous effects of groundwater and surface water management operations on freshwater ecosystems remains limited. This study combines a multi-decadal freshwater invertebrate dataset (1995-2016) with groundwater model outputs simulating the effects of different anthropogenic flow alterations (e.g. groundwater abstraction, effluent water returns) and river discharges. A suite of flow alteration- and flow-ecology relationships were modelled that tested different invertebrate community responses (taxonomic, functional, flow response guilds, individual taxa). Most flow alteration-ecology relationships were not statistically significant, highlighting the absence of consistent, detectable ecological responses to long-term water management operations. A small number of significant statistical models provided insights into how flow alterations transformed specific ecological assets; including Ephemeroptera, Plecoptera and Trichoptera taxa which are rheophilic in nature being positively associated with groundwater abstraction effects reducing river discharges by 0-15%. This represents a key finding from a water resource management operation perspective given that such flow alteration conditions were observed on average in over two-thirds of the study sites examined. In a small number of instances, specific invertebrate responses displayed relative declines associated with the most severe groundwater abstraction effects and artificial hydrological inputs (predominantly effluent water returns). The strongest flow-ecology relationships were recorded during spring months, when invertebrate communities were most responsive to antecedent minimum and maximum discharges, and average flow conditions in the preceding summer months. Results from this study provide new evidence indicating how groundwater and surface water resources can be managed to conserve riverine ecological assets. Moreover, the ensemble of flow alteration- and flow-ecology relationships established in this study could be used to guide environmental flow strategies. Such findings are of global importance given that future climatic change and rising societal water demands are likely to further transform river flow regimes and threaten freshwater ecosystems. Graphical abstract: Image, graphical abstract